How a Revolutionary Art Became Official Culture : Murals, Museums, and the Mexican State - Coffey, Mary K., 1968- (Book collections on Project MUSE., 2012)
This is a study of the reciprocal relationship between Mexican muralism and the three major Mexican museums-the Palace of Fine Arts, the National History Museum, and the National Anthropology Museum.